Co-encapsulação do trans-cinamaldeído e do fluconazol em nanopartículas de quitosana para o tratamento tópico da candidíase vulvovaginal - Sousa, Paulo Henrique Dantas de (2020)
Vulvovaginal candidiasis is an infection caused by fungi of the genus Candida. The increased incidence of vulvovaginal candidiasis maybe related to the advancement of chronic and immunosuppressive diseases along with the emergence of new mechanisms of fungal resistance. The objective of the present work was to prepare and characterize chitosan nanoparticles containing fluconazole and trans-cinnamaldehyde co-encapsulated for the topical treatment of vulvovaginal candidiasis. The empty nanoparticles, fluconazole, trans-cinnamaldehyde and coencapsulated were prepared using the ionotropic gelling technique. The nanoparticles were characterized as to their average size and polydispersity index by the dynamic light scattering technique. The surface charge of the nanoparticles was obtained by the electrophoretic migration technique. The empty nanoparticles had an average size of 448,9 ± 32,9 nm, PdI of 0,4 ± 0,1 and a surface load of 31 ± 0,4 mV, the nanoparticles of fluconazole exhibited an average size of 175,3 ± 8,9 nm, PdI of 0,2 ± 0,01, surface load of 33,2 ± 0,3 mV and encapsulation efficiency of 37,5% ± 3,1. Trans-cinnamaldehyde nanoparticles showed an average size of 352,6 ± 71,6 nm, PdI of 0,4 ± 0,05, surface load of 44,6 ± 3,7 mV and encapsulation efficiency of 44,6 % ± 3,7 and the coencapsulated nanoparticles had an average size of 234,5 ± 60,2 nm, PdI of 0,4 ± 0,07, surface load of 33,2 ± 0,5 mV and encapsulation efficiency of 56,8% ± 3 for fluconazole and 46,1% ± 5,1 for trans-cinnamaldehyde. The scanning electron microscopy of the nanoparticles presented an oval shape. The nanoparticles had their antifungal efficacy against the strain of C. albicans ATCC 10231 investigated by means of the minimum inhibitory concentration by the broth microdilution technique. The fluconazole nanoparticle showed antifungal efficacy with a minimum inhibitory concentration of 2 μg/mL and the trans-cinnamaldehyde was effective in the concentration of 75 μg/mL. The coencapsulated nanoparticle exhibited a minimum inhibitory concentration of 2 μg/mL for fluconazole and 37,5 μg/mL for trans-cinnamaldehyde. The coencapsulated nanoparticle exhibited the same minimal inhibitory concentrations as the fluconazole and trans-cinnamaldehyde nanoparticles. As for in vitro toxicity, nanoparticles were considered non-toxic. Regarding the in vivo toxicity test, only the empty nanoparticles exhibited a cytotoxic effect. All groups of nanoparticles proved to be effective in inhibiting fungal growth.